2017
DOI: 10.1128/genomea.00086-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Pseudomonas putida Strain GM4FR, an Endophytic Bacterium Isolated from Festuca rubra L

Abstract: Pseudomonas putida GM4FR is an endophytic bacterium isolated from aerial plant tissues of Festuca rubra L. Functional annotation of the draft genome (7.1 Mb) revealed 6,272 predicted protein-encoding genes. The genome provides insights into the biocontrol and plant growth-promoting potential of P. putida GM4FR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…These values are higher than the average of clusters found in the genomes of other Pseudomonas strains isolated from different origins. For example, recently published genomes of Pseudomonas strains isolated from soil or rhizosphere encode 9 (Hennessy et al, 2015 ), 13 (Vida et al, 2017 ) or 16 (Adam et al, 2015 ) of these clusters; in the same way, Pseudomonas strains isolated from plant tissues present 4 (Wemheuer et al, 2017 ) or 6 (Maggini et al, 2017 ) of these clusters. Most of these new genomes have revealed new potentially bioactive compounds in this genus, but importantly, many of the substances predicted in the genome sequences of the strains of this study have never been identified in other Pseudomonas strains.…”
Section: Discussionmentioning
confidence: 98%
“…These values are higher than the average of clusters found in the genomes of other Pseudomonas strains isolated from different origins. For example, recently published genomes of Pseudomonas strains isolated from soil or rhizosphere encode 9 (Hennessy et al, 2015 ), 13 (Vida et al, 2017 ) or 16 (Adam et al, 2015 ) of these clusters; in the same way, Pseudomonas strains isolated from plant tissues present 4 (Wemheuer et al, 2017 ) or 6 (Maggini et al, 2017 ) of these clusters. Most of these new genomes have revealed new potentially bioactive compounds in this genus, but importantly, many of the substances predicted in the genome sequences of the strains of this study have never been identified in other Pseudomonas strains.…”
Section: Discussionmentioning
confidence: 98%